Minimizing Level of Oksidative Stress in Martial Arts Atlhetes - Hakim, Abdul Latif Rahman; Nugroho, Fajar Adi; Septianingrum, Kartika (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This study aims to determine the extent of the effect of giving fruit with high levels of antioxidants on reducing stress levels in martial arts athletes. This study used an experimental method with 18 trials using a pretest-posttest control group design, with a true experimental laboratory research type. The sample of this study used 20 martial arts athletes. The subjects were divided into 2 groups, namely the control group and the experimental group (which consumed fruit with high levels of antioxidants). The data obtained came from taking cubital vein blood, then the blood samples were taken to the laboratory to determine the MDA levels using the TBARS method. Data analysis used 3 stages, namely normality test, homogeneity test, and hypothesis test. The results obtained in this study were: 1) The normality test obtained data on the significance value of each group> 0.05 so that the data was normally distributed; 2) The homogeneity test obtained data on the significance value of each group> 0.05 so that the data was homogeneously distributed; 3) The results obtained in this study were that fruit with high antioxidant levels could reduce stress levels in martial arts athletes. Keywords: Fruit with high levels of antioxidants, stress levels, in martial arts atlhetes